2013
DOI: 10.7124/bc.000817
|View full text |Cite
|
Sign up to set email alerts
|

Design and study of telomerase inhibitors based on G-quadruplex ligands

Abstract: In this review we have summarized the results of our recent research on telomerase inhibitors and G-quadruplex DNA ligands. A series of potential enzyme inhibitors were synthesized and studied. These compounds were based on tricyclic heteroaromatic systems (thiazolobenzimidazoles phenazines, acridones), amino-substituted cyanines and natural and synthetic porphyrins and their metalocomplexes. A number of compounds, including cyanines and especially porphyrin derivatives and conjugates, were found to efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Imidazophenazine is known as DNA intercalator [26,27], and we supposed that the attached dye would improve the binding of porphyrin to G4 structures by intercalation into double-stranded regions of telomeric DNA or between guanine quartets. Indeed, TMPyP 3+ -imidazophenazine hybrids and their zinc(II) and manganese(III) complexes efficiently inhibited telomerase and demonstrated antiproliferative activity in vitro at micro-and submicromolar concentrations [28].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazophenazine is known as DNA intercalator [26,27], and we supposed that the attached dye would improve the binding of porphyrin to G4 structures by intercalation into double-stranded regions of telomeric DNA or between guanine quartets. Indeed, TMPyP 3+ -imidazophenazine hybrids and their zinc(II) and manganese(III) complexes efficiently inhibited telomerase and demonstrated antiproliferative activity in vitro at micro-and submicromolar concentrations [28].…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is in perfect agreement with our recent experimental data on biological activity of the conjugates. Zn(II) complex was found to be several times more efficient telomerase inhibitor [36] and antiproliferative agent [33,36] than non-metallated hybrid.…”
Section: Discussionmentioning
confidence: 99%
“…Imidazophenazine is known as DNA intercalating agent [34,35], and we supposed that the attached dye would improve the porphyrin binding to G4 structures by intercalation between guanine quartets. It was shown that both TMPyP 3+ -ImPzn conjugate and its Zn(II) and Mn(III) complexes at low micromolar concentrations inhibit telomerase in TRAP assay and demonstrate antiproliferative activity in vitro [33,36]. The binding of these conjugates to intramolecular antiparallel G-quadruplex formed by model 22-mer oligonucleotide 5′-d[AGGG(TTAGGG) 3 ]-3′, a fragment of human telomeric DNA (Tel22, PDB code 143D), was studied using spectroscopic techniques [37].…”
Section: Introductionmentioning
confidence: 99%
“…They are considered as key regulatory elements in genome regions of biological significance, in particular, in human telomeres and promoter regions of some proto-oncogenes [10][11][12][13]. They are known as promising targets for anticancer therapy, since G-quadruplex binding ligands, including many porphyrin derivatives, are able to inhibit the telomerase, a tumor-associated enzyme responsible for telomere elongation [14][15][16]. We have recently found that CatPheo-a inhibits the telomerase in vitro at low micromolar concentrations being much more active than its precursor, anionic Pheo-a.…”
Section: Introductionmentioning
confidence: 99%